18F-fluorodeoxyglucose positron emission tomography/computed tomography in the diagnosis of suspected paraneoplastic syndromes: A retrospective analysis - Bresler, Richard; Schroeder, Harry William III; Chow, David Z.; Lim, Ruth (World Journal of Nuclear Medicine, 2020)
Paraneoplastic syndromes are a rare clinical presentation of tumor thought to affect 0.01% of patients with cancer. Paraneoplastic syndromes present a diagnostic challenge as a wide variety of signs and symptoms may appear. This study examines the use of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) as a diagnostic imaging tool for detecting tumor in suspected paraneoplastic syndrome cases. This single-center retrospective study included patients with suspected paraneoplastic syndrome who underwent whole-body 18F-FDG PET/CT scan between December 2005 and December 2016. Associated clinical data were gathered via electronic chart review. Patient records were reviewed for age, sex, clinical signs and symptoms, ancillary diagnostic procedures, date of diagnosis, and follow-up time. Ninety-nine patients met inclusion criteria for this study. Mean follow-up period was 1.8 years. Cancer prevalence was 12.1%. The 18F-FDG PET/CT results are as follows: 10 true positives, 5 false positives, 82 true negatives, and 2 false negatives. The diagnostic values are as follows: sensitivity 83.3%, specificity 94.3%, positive predictive value 66.7%, and negative predictive value (NPV) 97.6%. The high NPV in our study supports the effectiveness of 18F-FDG PET/CT to rule out tumor in suspected paraneoplastic syndrome. Future research aims to analyze which patients with suspected paraneoplastic syndrome would benefit most from 18F-FDG PET/CT.
Keywords: Oncology; paraneoplastic syndrome; positron emission tomography/computed tomography